2020
DOI: 10.1017/s2045796020000384
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antidepressants for cessation therapy in betel-quid use disorder: a randomised, double-blind, placebo-controlled trial

Abstract: Aims More than one-half of betel-quid (BQ) chewers have betel-quid use disorder (BUD). However, no medication has been approved. We performed a randomised clinical trial to test the efficacy of taking escitalopram and moclobemide antidepressants on betel-quid chewing cessation (BQ-CC) treatment. Methods We enrolled 111 eligible male BUD patients. They were double-blinded, placebo-controlled and randomised into three treatment groups: escitalopram 10 mg/tab daily, moclobemide 150 mg/tab d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…The interaction between the follow-up time and SSRI treatment was only significantly decreased at the four-week follow-up. The study of Hung et al demonstrated that a reduction in daily BQ consumption after antidepressant therapy, including MAO-A inhibitors and SSRIs, was observed among patients with depression [ 47 , 48 ]. Our study and previous clinical trials provide preliminary evidence for appropriate treatments for the cessation of AN addiction.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between the follow-up time and SSRI treatment was only significantly decreased at the four-week follow-up. The study of Hung et al demonstrated that a reduction in daily BQ consumption after antidepressant therapy, including MAO-A inhibitors and SSRIs, was observed among patients with depression [ 47 , 48 ]. Our study and previous clinical trials provide preliminary evidence for appropriate treatments for the cessation of AN addiction.…”
Section: Discussionmentioning
confidence: 99%
“…A limited number of behavioral and pharmacologic interventions to assist cessation of areca nut use have been reported recently ( Moss et al 2015 ; Hung, Lee, Chung, et al 2020 ; Hung, Lee, Ko, et al 2020 ). The total duration of these interventions was far too short to demonstrate any effectiveness on cancer incidence.…”
Section: Evidence For Carcinogenicity Of Areca Nut In Humansmentioning
confidence: 99%
“…As yet there still are no established areca nut cessation guidelines in populations of patients with areca nut habits, let alone those with OSF. A recent RCT lasting 8 weeks demonstrated that the anti-depressants escitalopram (SSRI) or moclobemide (MAO inhibitor) led to a reduction in betel quid use compared to placebo (Hung et al, 2020). A feasibility study (Moss et al, 2015) has paved the way for an ongoing NIH-funded trial to explore the efficacy of an intensive group-based areca nut cessation program (ClinicalTrials.…”
Section: Or Al Sub Mucous Fib Ros Ismentioning
confidence: 99%